Digital tooling with soft power to drive the smart silver economy under the aged society of Thailand - Lomchavakarn, Piyachat (Edelweiss Applied Science and Technology, 2024)
“Thailand 4.0” is the current national strategic plan driven by digital technology and innovation; “Silver Economy” is one among the urgent flagship to serve the urgent needs of aged society with its approximately 20-30 percent of Thai population. Besides, around 60 percent of the elderly proven being under the poverty line. Most of the urgent demands is economics opportunities, digital skills, and health care, respectively. Objectives are 1) the current situation of elderly towards “Silver Economy” embedded with “Soft Power”; 2) the digital literacy & competency skills of elderly towards “Silver Economy” embedded with “Soft Power”; and 3) the recommendation to support the elderly towards “Silver Economy” embedded with “Soft Power”. Mix research methods were used 1) Quantitative research by e-survey among the 100 elderlies across the country who involved with Silver Economy and Soft Power. Qualitative research by in-depth-interview and Focus Group Discussion among 15 key informants from the elderly and all stakeholders. Results found 1) most of the elderly have a very good attitude, high demands to run their Silver Economy activities especially with their own Soft Power; 2) most of the elderly gain fundamental digital literacy & competency. More digital top skills are needed to run their Silver Economy activities i.e., creative digital marketing skills, AI in digital PR, digital storytelling, and local tourism, etc. and 3) Recommendations for more tangible collaborations among all the relevant stakeholders from policy to the practical agencies. Friendly and effective portal for all kinds of collabolations among the stakeholders and the elderly themselves.